Assinaturas da violação da simetria de Lorentz na radiação cósmica de fundo - Araújo, Arilo Pinheiro (2016)
In this paper we investigate the relationship of violation of Lorentz symmetry with the anisotropy of the cosmic microwave background. We shall set out the development of the understanding of the Big Bang and also radiation in question and show its meaning and its nature. We show the symmetry settings Lorentz and violation of Lorentz symmetry. We will use the Bumblebee model to deal with terms that violate this symmetry and show which terms are used. We develop a Einstein's equation modified by varying with respect to the metric of the Einstein-Hilbert action with the terms of added Bumblebee, as are the terms that violate Lorentz symmetry. We will use this equation developed to make a perturbation analysis. We will use the Friedmann-Lemaître-Robertson-Walker metric, being an isotropic metric, and introduce a disturbance in each direction of the spatial part of the metric in question to make it anisotropic. Finally, we present a set of four coupled linear differential equations (with disorders such as variables) which relate to proposals disorders Bumblebee field.